THE GROTESQUENESS IN VIETNAMESE FOLK JOKES - Quoc Minh Duong Dang (Tạp chí Khoa học Đại học Đà Lạt, 2024)
Grotesqueness exploits laughter, exaggeration, and unusual contrasts between the imaginary and the real, beauty and ugliness, tragedy and comedy. Grotesqueness is prevalent in folk jokes, especially in tales about gluttony, henpecked husbands, and sexual desire. It manifests itself through character type, language, tone, and time frame. Using analytical and synthetic methods and an interdisciplinary approach, the author examines Vietnamese folk jokes to elucidate this viewpoint.